Coverless Text Information Hiding Based on Built-in Features of Arabic Scripts - Sabaa Hamid Rashid; Dhamyaa A Nasrawi (Bright Publisher, 2024)
Text steganography is crucial in information security due to the limited redundancy in text. The Arabic language features offer a new method for data concealment. In this paper, the researchers propose a new coverless text information hidingmethod based on built-in features of Arabic scripts. The first word of each row in the dataset is tested based on eight features to get one byte containing 1 or 0. That is a result of the presence or absence of the following features: mahmoze, diacritics, isolated, two sharp edges, vowels, dotted, looping, and high frequency.Then, each byte is converted to a decimal number (ASCII code) to implement a dynamic mappingprotocol with the most frequent letter.In the hiding process, each character in the secret message is converted to ASCII code and successfully matched in the dataset. Thus, after matching, the candidate text is sent to the receiver. In contrast, the pre-agreed dynamic mappingprotocol was implemented in a receiver to extract secret messages. Three Arabic datasets are used in this paper (SANAD (Single-Label Arabic News Articles Dataset) includes 45500 articles, Arabic Poem Comprehensive Dataset (APCD) contains 1,831,770 poetic verses in total, Arabic Poetry Dataset contains more than 58000 poems). The suggested approach withstands existing detecting methods because of no modification or generation. Moreover, there is an enhancement in hiding capacity, which can conceal a (character /word). Hence, all the messages are embedded successfully using dynamic mapping.